Dietary Supplementation of Monensin for Methane Mitigation in Non Pregnant Non Lactating Murrah Buffaloes - gupta, shiva (Indian Journal of Animal Nutrition, 2018)
ABSTRACT- The present study was conducted to evaluate the effect of dietary monensin supplementation on nutrient utilization and enteric methane emission in non pregnant non lactating Murrah buffaloes. Fourteen dry Murrah buffaloes were randomly divided into two groups of seven animals each based on body weight. Both groups were fed as per ICAR, (2013) without and with monensin supplementation (350 mg/head/day) in control and treatment group, respectively for sixty days. The daily nutrient intake (kg/d) and apparent digestibility (%) of nutrients were similar (P>0.05) in both the groups. However, Enteric CH4 emissions (g/d) was found to be reduced by 10.09% in monensin supplemented group as compared to control and lowered (P